Design and analysis of a portal frame test rig for vertical load testing of goalpost pipeline support - Ghazali, Tsaqif Al Farrel; Yob, Mohd Shukri; Abd Latif, Mohd Juzaila; Kurdi, Ojo; Munir, Fudhail Abdul (International Journal of Advances in Applied Sciences, 2025)
Pipe support is a crucial infrastructure in the oil and gas industry, requiring robust designs to withstand various loads and maintain operational stability. While numerical analysis is commonly used to assess the interaction between pipelines and supports, experimental testing remains essential for validation. However, field testing is often costly and difficult due to safety constraints. To overcome this, a reliable test rig with minimal deflection is needed to ensure accurate experimental results. This study uses finite element analysis (FEA) to evaluate both a goalpost pipeline support and a newly developed portal frame test rig. The test rig was analyzed under two conditions: the failure load of the goalpost support and an amplified load with a factor of 2.5 to simulate unexpected scenarios. Results show the test rig can safely withstand loads up to 40 kN, meeting the EN 1990 safety factor requirement of 1.5. Furthermore, critical components remained within the deflection limit specified by the British Constructional Steelwork Association (BCSA), which is under L/1,000 of the beam length. These results confirm the structural integrity and suitability of the portal frame test rig for accurate testing of the goalpost pipeline support structure.